IIntegration of traditional and digital strategies development of fashion brands on marketplaces - O. G. Kariaka (Путеводитель предпринимателя, 2025)
The article analyzes the prospects for integrating traditional and digital methods of promotion in the fashion brand industry on marketplaces. The relevance of the topic is due to the expansion of the digital environment and the growing demand for clothing through online platforms. The novelty of the study is that it details the process of combining offline and online tools that lead to increased brand awareness and customer loyalty. The work describes multichannel strategies that involve advertising, interaction in social networks and technological innovations. Approaches to the formation of product cards, the use of reviews and the introduction of interactive services are studied. Particular attention is paid to the ecology and virtual format of digital fashion. The objective of the study is to provide a scientific basis and practical recommendations for companies seeking to strengthen their positions on marketplaces. The methods include comparative analysis, a review of literary sources and an assessment of the collected statistical data. The conclusion reflects the findings on the value of continuous improvement of promotion strategies. The article is useful for fashion industry researchers, marketers and brand managers.